Receptores ACE-2 en superficie ocular y susceptibilidad con SARS CoV-2 (2021)
The World Health Organization declared the infection named COVID-19 as a Public Health Emergency of International Concern on January 30, 2020, caused by the RNA virus called Coronavirus, causing more than 800 thousand deaths worldwide.(1) According to research carried out by Piera Valenti, they describe: “Coronavirus belongs to the Coronaviridae family, specifically of the Delta genus. coronavirus and its name is SARS-CoV-2” (2); This virus is similar to the SARS-CoV at the nucleotide level, and possesses a sense single-stranded RNA genome positive with predisposition to epithelial cells and the respiratory system; this virus contains an encapsulated form that has a spike glycoprotein interacting with the receptor binding domain. The purpose of this bibliographical study is to understand and analyze that the virus does not It only affects the heart, lungs, kidneys, liver, digestive tract, and liver. blood vessels, but there is also growing clinical and scientific evidence of that the human ocular surface may represent an additional route of entry. In the evidence has shown that some respiratory viruses, including SARS CoV cause eye complications such as conjunctivitis in infected people and in they do establish a respiratory infection after ocular exposure.